Structure of the uvrB gene of Escherichia coli. Homology with other DNA repair enzymes and characterization of the uvrB5 mutation. - Backendorf, C (1986)
The complete nucleotide sequence of the Escherichia coli uvrB gene has been determined. The coding region of the uvrB gene consists of 2019 nucleotides which direct the synthesis of a 673 amino-acid long polypeptide with a calculated molecular weight of 76.614 daltons. Comparison of the UvrB protein sequence to other known DNA repair enzymes revealed that 2 domains of the UvrB protein (domain I = 6 amino acids, domain II = 14 amino acids) are also present in the protein sequence of the uvrC gene. We show that the structural homologies between UvrB and UvrC are as well reflected by the cross-reactivity of anti-uvrB and anti-uvrC antibodies with UvrC and UvrB protein respectively. In the N-terminal part of UvrB, domain III (17 amino acids) shows a strong homology with one part of the AlkA gene product. Adjacent to domain III, an ATP binding site consensus sequence is found in domain IV. The uvrB5 mutant gene from strain AB1885 has been cloned on plasmid pBL01. We show that the uvrB5 mutation is due to a point deletion of a CG basepair and results in the synthesis of an 18 kD protein composed of the 113 N-terminal amino acids of the wild type uvrB gene and a 43 amino acid long tail coded in the -1 frame.